The Role of Mediation in Land Dispute Resolution: Effectiveness and Challenges - Jumra; Tarmizi; Rasyid, Mukhawas; Suriyati (Journal of Indonesian Scholars for Social Research, 2024)
Land disputes are one of the most common types of conflict in Indonesia, given that land has a very high economic, social and cultural value. As development and land use changes increase, disputes over ownership, boundaries, and land use rights are increasingly common. Mediation as an alternative to out-of-court dispute resolution has been recognised as a faster, cheaper and more efficient method of resolving often complex and sensitive land conflicts. This study analyses the various factors that influence the success of mediation in land dispute cases, including the role of the mediator, legal support, as well as the readiness of the parties involved. The results show that mediation can be an effective tool for resolving land disputes, especially when supported by competent mediators and a strong desire from the parties to reach an agreement. However, the research also identified a number of challenges, such as the power imbalance between the parties, the lack of understanding of the mediation process, as well as limitations in the implementation of mediation outcomes. Thus, while mediation offers great potential in land dispute resolution, further efforts are needed to overcome these obstacles in order for mediation to function optimally in the context of agrarian law in Indonesia.